Inter- and intra-annual ring width and δ13C responses to drought in tree species of a laurel cloud forest (Tenerife, Canary Islands) - Camarero, J. Julio; González-Rodríguez, Águeda M.; Valeriano, Cristina; Fernández-Marín, Beatriz; Tamudo, Elisa; Rinne-Garmston, Katja T.; Miranda, José Carlos (Elsevier, 2025)
Subtropical cloud forests grow under particular climate conditions characterized by narrow thermal ranges, high relative humidity and low radiation levels. These diverse ecosystems include many endemisms and are threatened by climate and anthropogenic land-use pressures, particularly in islands. This is the case of some laurel cloud forests found in Macaronesian archipelagos such as the Canary Islands. To assess growth response to climate variability, we studied tree-ring series in three evergreen species (the Macaronesain endemisms Laurus novocanariensis and Morella faya, and the editerranean Prunus lusitanica) co-occurring in a laurel cloud forest (Anaga) located in Tenerife, Canary Islands, Spain. The intra-annual wood δ13C was also measured in the rings formed from 2011 to 2013 in two of these species (L. novocanariensis, P. lusitanica) to determine how they responded to the severe 2012 drought. Sampled trees were young (age ranged from 33 to 54 years). L. novocanariensis and P. lusitanica presented the highest (2.44 mm) and lowest (1.84 mm) mean growth rates, respectively. Wet, cool and foggy conditions in the prior winter enhanced the growth of L. novocanariensis and M. faya, whereas P. lusitanica was less responsive to climate variability. The tree-ring δ13C values were higher in P. lusitanica (mean ± SE = − 26.10 ± 0.07 ‰) than in L. novocanariensis (-26.56 ± 0.08 ‰), and the difference intensified during the dry year of 2012. In P. lusitanica, δ13C values decreased as the number of foggy days increased. These findings demonstrate species-specific differences in growth and δ13C responsiveness to climate. The study of these proxies at different temporal resolutions highlights how reduced fog input and drought, affecting atmospheric water demand and soil moisture availability, respectively, constrain tree growth in laurel cloud forests.
Keywords: dendroecology; drought stress; intra-annual δ13C analyses; Laurisilva; Laurus novocanariensis; Morella faya; Prunus lusitanica